2013
DOI: 10.1371/journal.pone.0066364
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Expression in CD4 Positive Cells of the Japanese Pufferfish, Takifugu rubripes

Abstract: CD4+ T (Th) cells are a central component of the adaptive immune response and are divided into distinct sets based on their specific cytokine production pattern. Several reports have suggested that fish possess Th subset activity similar to that of mammals. The aim of the present study was to isolate CD4+ T cells from the blood of Japanese pufferfish, Fugu rubripes, and to characterize their cytokine expression profile. We produced a specific antibody against Fugu CD4 and performed cell sorting with the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…To our knowledge, this is the first time that CD4-1 + T cells are demonstrated to exist in rainbow trout, and the results are in agreement with previous studies reporting that cells from the spleen, thymus, and gut of trout express CD4-1 transcripts and T cell marker homolog genes (13,33). Recent studies also reported the presence of CD4-1 + T cells in other fish species such as ginbuna crucian carp and fugu using CD4-1-specific Abs (18,19). The presence of this type of lymphocyte subset in salmonids, fugu, and carp, which evolved quite separately, is evidence of the conservation of this subpopulation of T cells in teleost fish.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, this is the first time that CD4-1 + T cells are demonstrated to exist in rainbow trout, and the results are in agreement with previous studies reporting that cells from the spleen, thymus, and gut of trout express CD4-1 transcripts and T cell marker homolog genes (13,33). Recent studies also reported the presence of CD4-1 + T cells in other fish species such as ginbuna crucian carp and fugu using CD4-1-specific Abs (18,19). The presence of this type of lymphocyte subset in salmonids, fugu, and carp, which evolved quite separately, is evidence of the conservation of this subpopulation of T cells in teleost fish.…”
Section: Discussionsupporting
confidence: 92%
“…Sorted CD4 + cells from fugu PBLs expressed T cell marker genes and were able to upregulate the expression of Th1, Th17, and Treg cytokines and downregulate the expression of Th2 cytokines after stimulation with LPS, poly(I:C), or Con A, suggesting that these cells exhibit a similar pattern of Th-specific cytokine expression to that seen in mammals (19). Somamoto et al (20) provided evidence that CD4-1 + cells from ginbuna crucian carp help to induce a secondary Ab response in vivo, suggesting a conservation of the Th cell function in teleost fish.…”
Section: T He Cd4mentioning
confidence: 89%
“…In the absence of those, transcript levels have been used to assess expression patterns of cd4-1 and cd4-2 , but results in teleosts have been inconclusive. For example, flounder cd4-1 and cd4-2 transcripts are expressed in mutually exclusive cell types (21) while transcript analysis of sorted CD4-1 + cells in zebrafish, ginbuna carp, and fugu suggests the existence of cells expressing CD4-1 and/or CD4-2 (2224). Due to the poor characterization of teleost CD4 + leukocytes, very few functional studies have been carried out on these cells.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it has been reported that CD4-1 + cells in ginbuna carp and zebrafish undergo antigen-specific proliferation (2527). With regards to cytokine expression, zebrafish and fugu CD4-1 + cells can produce T-cell related cytokines in response to stimulation with TLR ligands and specific antigen (22, 24); however the expression of such cytokines upon pathogen challenge remains to be studied. The only study performed on teleost CD4-2 + cells suggests that these leukocytes represent a regulatory T cell (Treg)-like phenotype in pufferfish (28).…”
Section: Introductionmentioning
confidence: 99%
“…ConA, a member of the lectin family of plant proteins (12), non-specifically activates T cells (13,14). General immune responses to LPS and ConA have been studied in several species including murine (15)(16)(17), porcine (18)(19)(20), fish (21)(22)(23), and humans (7,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%